Strategic software quality management : how to incorporate sustainable continuous improvement practices - Fidanboy, Mahsa; Fidanboy, Cemalettin Öcal (Routledge, Taylor & Francis Group, 2025)
This book, by bridging software quality management and strategic management, can be used by software quality practitioners for effective results. The software development process is usually studied with regards to its functional aspects and the attempts to improve the quality and performance are mainly concentrated on the technical side.
"A Productivity Press book."
Keywords: Computer software -- Quality control.; Computer programming -- Management.; Software engineering.; elektronické knihy; electronic books